Trust in Government and Tax Compliance in Indonesia and Malaysia: Do Ethics and Tax Amnesty Matter? - Novita, Santi; Somya Lasmana, Mienati; Mohd Yusof, Nor Azrina; Safeei, Roshidah; Chai Chuen, Lee (International Journal of Economics and Financial Issues, 2024)
This study examines the moderating role of tax amnesty and the mediating role of ethics in the relationship between trust in government and tax compliance among taxpayers in Indonesia and Malaysia. The data were analysed using the structural equation modeling to examine the mediating role of ethics and hierarchical regression analysis to test the moderating role of tax amnesty in the relationship between trust and tax compliance. Based on the sample collection using the purposive sampling method, the study included 529 respondents from Indonesia and 137 from Malaysia. The findings reveal that the relationship between trust in government and taxpayer compliance is statistically significant with ethics as full mediator in Indonesia. However, the relationship between trust in government and tax compliance is not statistically significant in Malaysia. Ethics has a direct effect on tax compliance in both countries. Tax amnesty does not show a moderating effect in the relationship between trust in government and tax compliance. However, it plays a negative predictive role for tax compliance in Indonesia. This study will assist the government in developing tax compliance strategies to increase tax revenue with the launch of a similar program without neglecting the honest taxpayer.